ANALISIS PENGARUH EFISIENSI MODAL KERJA, LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2011 -2014 - Dyah A., Erwin; Kholifah, Umi (JEM17: Jurnal Ekonomi Manajemen, 2016)
Research on the influence of the efficiency of working capital, liquidity and solvency to profitability on industrial consumer goods intends to analyze effect to working capital efficiency, liquidity and solvency to profitability on industrial consumer goods. The research data acquired of financial statements (secondary) and processed using SPSS 22.0 program. Objects of this research were industrial consumer goods companies listed on the Indonesian Stock Exchange (ISE) in the period 2011 to 2014 with sample of as many as 16 companies. The results of research to point out that : (1) Partially only variable working capital turnover (WCT) and the current ratio (CR) which has a significant influence on the return on investment (ROI) while the variable debt to equity ratio (DER) was not proven significant effect on return on investment (ROI), it is confirmed from the results of t-test showed significance level obtained from variable working capital turnover (WCT) and the current ratio (CR) is smaller than the standard used is 0% and 3,3% from 5% whereas the level of significance of variable debt to equity ratio (DER) is greater than the standard used is 23,7% of 5%. (2) simultaneously, working capital turnover (WCT), current ratio (CR) and debt to equity ratio (DER) on return on investment (ROI) have a positive and significant effect on return on investment (ROI), which is evident from the results of the f-test showed significance level obtained is smaller than the standard used is 0% from 5%. (3) Variable working capital turnover (WCT) has a dominant influence on the return on investment (ROI) with a correlation obtained by 25,71%.Keywords : working capital efficiency (WCT), liquidity (CR), solvency (DER), profitability (ROI), industrial consumer goods companies.